2021
DOI: 10.1002/ab.21954
|View full text |Cite
|
Sign up to set email alerts
|

Ecological contexts of youth antisocial behaviors: A longitudinal perspective

Abstract: The current study examined and compared the relative influence of ecological factors on youth antisocial behaviors (i.e., aggression and rule‐breaking) using longitudinal data while assessing the moderating effect of youth attention‐deficit/hyperactivity disorder (ADHD) diagnosis. The study used the fifth and sixth wave of data from the Fragile Families and Child Wellbeing Study (n = 2595; mean age = 9.26 at wave five) for the analysis. Multivariate models show that youth ADHD, physically and psychologically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…When parental home or any other caregiving environment does not provide youth with resources and supports necessary for them to feel safe, protected, and to develop they may resort to delinquent and antisocial behaviors (Zhang et al, 2021). In such an unsupportive environment, negative peer influences may strongly predict youths’ antisocial behaviors.…”
Section: How Context/setting Informs Negative and Positive Peer Influ...mentioning
confidence: 99%
“…When parental home or any other caregiving environment does not provide youth with resources and supports necessary for them to feel safe, protected, and to develop they may resort to delinquent and antisocial behaviors (Zhang et al, 2021). In such an unsupportive environment, negative peer influences may strongly predict youths’ antisocial behaviors.…”
Section: How Context/setting Informs Negative and Positive Peer Influ...mentioning
confidence: 99%
“…Antisocial personality disorder was likewise related to adverse experiences in youth such as child abuse and neglect [31]. An additional longitudinal study examining AB and ecological factors found abusive parenting, peer victimization, and community cohesion to be important predictors of AB in children and adolescents with ADHD [32]. It has thus been repeatedly shown that being the victim of violence, or indeed merely observing violence in childhood, is a potent predictor of AB [33].…”
Section: Introductionmentioning
confidence: 99%